EFFORTS TO IMPROVE EARLY CHILDHOOD SCIENCE ABILITIES THROUGH THE COLOR MIXING EXPERIMENTAL METHOD - Aisyah Oktavia Siregar; Arnita Fitri; Anelvi Novita Sari; Maiyida Safita (Yayasan Amanah Nur Aman, 2026)
This research is a literature review aimed at understanding efforts to improve early childhood science skills through the color-mixing experiment. The method used in this article is a literature review, which served as initial preparation for developing a research framework. In this literature review, the researcher utilized various written sources, such as articles, journals, and documents relevant to the research. The literature review revealed an improvement in early childhood science skills. The learning process focused on color-mixing games to improve children's science skills. Several studies have shown that color-mixing games can improve early childhood science.